Professor Pincushion's beginner guide to sewing : garment making for nervous newbies - Opatrny, Tova, 1978- (Stash Books, an imprint of C&T Publishing, Inc., 2022)
"Professor Pincushion's Beginner Guide to Sewing is part textbook, part how-to, and all cheeky fun. Follow along with information on sewing tools and supplies, how to read commercial patterns and sewing techniques commonly used in garment sewing. Inside are five projects perfect for new and skilled sewers"-- Provided by publisher"--